Revisiting Friedrich Engels’s Dialectics of Nature in an Age of Digital Idealism - Christopher Leslie (tripleC: Communication, Capitalism & Critique)
The idealism that Fredrich Engels seeks to defeat in Dialectics of Nature today pervades online discourse and pedagogies of science, technology, engineering, and mathematics (STEM). The deterministic view that STEM is dedicated to unleashing the inherent power in objects for the service of privileged societies fails to understand the basic principles that Engels proposed. Engels exposes his contemporaries’ flawed understanding of science and technology and provides interdisciplinary examples that exemplify a different way of thinking. Outside of China, Engels’s ideas have been used to suggest that social considerations cannot be a part of science because they limit the free exchange of ideas. Within China, particularly after the establishment of the People’s Republic in 1949, these ideas have been the basis of new thinking about the relationships among developers, the government, and the people. Moreover, readers of Dialectics of Nature who are familiar with the basic tenets of Science and Technology Studies (STS), such as social constructivism and actor-network theory, will not be so impressed with the idea that social theory has no place in understanding science and engineering. This analysis suggests avenues of cooperation for international science studies. In addition, it provides a starting point for pedagogies to promote a development of science and technology that reduces inequality and supports the notion that the liberal arts have an important place in the study of science and engineering, an insight known as STEAM.